2007
DOI: 10.1111/j.1471-0307.2007.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Property changes and cholesterol‐lowering effects in evening primrose oil‐enriched and cholesterol‐reduced yogurt

Abstract: The present study was carried out to investigate the changes in chemical and sensory properties and the cholesterol‐lowering effect of evening primrose oil (EPO) addition to cholesterol‐reduced yogurt. The rate of cholesterol removal reached 93.5% by β‐cyclodextrin in yogurt before EPO addition. pH, viscosity and microbial counts decreased with amounts of EPO added. The thiobarbituric acid value of cholesterol‐reduced and EPO‐enriched yogurt increased proportionally to length of storage period and amount of EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
40
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 14 publications
9
40
1
Order By: Relevance
“…Apparent viscosity of enriched yogurt increased until day 14 and then decreased but apparent viscosity of control yogurt increased until day 7 and then decreased. It was reported that the apparent viscosity of yogurt during storage time decreases (Lee et al 2007;Supavititpatana et al 2010), while Sahan et al (2008) reported that apparent viscosity can increase over time due to the rearrangement of protein and protein-protein contacts. Figure 2 shows chromatogram of standard solution, peak identification left to right: Brasicasterol, stigmasterol, campesterol and β-sitosterol.…”
Section: Apparent Viscositymentioning
confidence: 98%
“…Apparent viscosity of enriched yogurt increased until day 14 and then decreased but apparent viscosity of control yogurt increased until day 7 and then decreased. It was reported that the apparent viscosity of yogurt during storage time decreases (Lee et al 2007;Supavititpatana et al 2010), while Sahan et al (2008) reported that apparent viscosity can increase over time due to the rearrangement of protein and protein-protein contacts. Figure 2 shows chromatogram of standard solution, peak identification left to right: Brasicasterol, stigmasterol, campesterol and β-sitosterol.…”
Section: Apparent Viscositymentioning
confidence: 98%
“…In recent years, a number of studies have indicated that cholesterol removal from food products such as milk, cream, butter, lard, egg yolk and cheese was most effectively achieved by powdered b-cyclodextrin (b-CD) treatment [1][2][3][4][5][6][7][8][9]. b-CD is a cyclic oligosaccharide composed of a(1?4) linkages of seven glucose units.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some methods require high investment and operation costs (Yen and Tsai 1995;Kwak et al 2002). Research studies show that cholesterol can be removed from milk and dairy products, egg yolk, lard, by using b-cyclodextrin (b-CD) (Yen and Tsai 1995;Krause et al 2007;Lee et al 2007;Seon et al 2009). …”
Section: Introductionmentioning
confidence: 99%